Granule size informs the characteristics and performance of microalgal-bacterial granular sludge for wastewater treatment - Zhang, Meng (2022)
In this study, four groups of microalgal-bacterial granules with averaged diameters of about 356, 760, 951 and 1,444 µm were used to investigate their characteristics and performance in treating wastewater. A strong correlation between extracellular polymeric substances of microalgal-bacterial granules and the granule size was observed. Moreover, granule size showed a positive effect on the specific organics removal rate, but being negative for ammonium and phosphorus removal. It appeared that granule size could be used as a useful index to reflect the synergistic interactions between microalgae and bacteria in terms of the abundances, distributions and functional species in the microalgal-bacterial granules. This study is expected to offer new insights into the size-dependent performances of microalgal-bacterial granules for wastewater treatment.